Psychological Distress among Libyan Mothers of Autistic Male Children in Tripoli, Libya - Aisha Benrween; Tarek Alazabi; Hanin Abukash; Nermen Alnajjar; Nawal Ejdeah; Maysam Shileebik; Mahmoud Alharari; Mouad Tellib; Mohammed Alborai (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. The impact of caring for a child with autism has been observed among mothers of children with autism spectrum disorders (ASDs) in western countries; however, there is a scarcity of data in the Arab countries. The study aimed to assess the magnitude of psychological distress among the mothers of autistic children and find out the associations between the psychological distresses of mothers with their socio-demographic characteristics, and with their autistic children’s socio-demographic characteristics. Methods. A case series study was conducted among Libyan mothers of autistic children in the Centers of Special Education for Autism Children and Neurodevelopment Clinic of AI-Khadra Hospital in Tripoli. The General Health Questionnaire 28 (GHQ-28) was used to find out the proportion of probable psychiatric disorder. Data analysis was performed by using the SPSS version 20. Results. A total of 104 mothers of autistic children participated in the study, their mean age was 37.9 (SD=7.7) years, and the majority of them were Tripoli residents (67.3%). Half of the mothers were university graduates, though 46.2% of them were housewives, all of the children were males, with mean age of (7.1 ± 3.1) years. The most type of autism was autistic spectrum disorder (56.7%) and also delayed development was present in 58.7% of them. The psychological Distress Status of mothers was 53%. Furthermore, out of all studied variables, the bivariate analysis showed a statistically significant association between the psychological distress of mothers with their residency and with the number of family members (P=0.017, P=0.020; respectively). Conclusion. The mothers of children with autism had significant psychological problems. Providing some programs to support families (especially mothers) that can strengthen family coping, and made coping strategies for parents with an autistic child is worth.